The influence of the synectics mind maps cooperative learning (SM2CL) model on the students learning outcomes of class XI MAN Gowa - Riskawati, Riskawati; Mustami, Muhammad Khalifah; Afif, Ahmad (Journal of Islam and Science, 2023)
Character education in subjects needs to be implemented through various methods that can invite students to reason and build networks. The aims of this study were to: (1) Find out the learning outcomes of students in class XI MAN Gowa who were taught using the SM2CL learning model; (2) Find out the learning outcomes of Class XI MAN Gowa students who are taught without using the SM2CL learning model; and (3) Examine the effect of the SM2CL learning model on the learning outcomes of class XI MAN Gowa students. This research is a type of quantitative research, namely a quasi-experimental research with a nonequivalent control group design The population of this study is the students of MAN Gowa class XI with a total of 170 people and the research sample totaling 68 students selected by purposive sampling technique. The instruments used for learning outcomes are multiple choice questions for cognitive and observation sheets for affective and psychomotor learning outcomes. The data analysis technique used is descriptive analysis and inferential analysis using prerequisite test and t-paired sample test. Results of the study are (1) The learning outcomes of the experimental group students class XI IPA II on cell material taught using the SM2CL learning model, the average value of learning outcomes was 75.85, which was included in the high category; (2) Learning outcomes of control group students class XI IPA I on cell material taught using the cooperative learning model, the average value of learning outcomes was 63.73 including in the medium category; and (3) There is an effect of the SM2CL learning model on learning outcomes in class XI IPA II MAN GOWA students. This is evidenced by the results of hypothesis testing using the paired t test, the results obtained sig (2 tailed) or p-value smaller than 0.05, namely 0.000 <0.05 or H1 is rejected and H0 is accepted. This study implies learning activities using the SM2CL learning model have an influence on student learning outcomes, therefore this model can be considered for use in the learning process, especially if it is related to improving learning outcomes.